(untitled) (KSV Journal of Pharmacy and Health Sciences, 2024)
A simple, precise and sensitive HPLC method has been developed for the estimation of fedratinib in pharmaceutical dosage Form form using C18 column Shimadzu ((250 mm × 4.6 mm, 5 µm)) with a mobile phase of HPLC grade Phosphate Buffer, pH 5.0 and HPLC grade acetonitrile. The mobile phase was sonicated for 10 min and filtered through a 0.45µm membrane filter at a flow rate of 1.0mL/min. The detection was carried out at 290nm and retention time of fedratinib was found to be 2.90 min. Linearity was observed in the concentration range of 25-75 µg/mL (coefficient of determination R2=0.9987) with regression equation y = 10527x - 18715. The method was validated as per ICH guidlines.